A study of methods for estimating the cell content of bulk milk - J. K. L. Pearson; C. L. Wright; D. O. Greer (Journal of Dairy Research, 1970)
Summary Four methods of estimating the cell content of bulk milk were studied, correlated statistically and their degree of reproducibility estimated. The relative merits of the 4 methods are discussed, and the need for defining the object of testing before selecting a test is stressed. If designed for use in a programme for mastitis control, or the control of milk quality based on cell content, each country must choose a screening test or a precise cell-counting technique, depending on the availability of laboratory resources, extension advisory services and other economic factors. Screening tests studied were the California Mastitis Test (CMT) and the Brabant Mastitis Test (BMR), the former showing a correlation coefficient of 0·817 against the Electronic Cell Count (ECC) method in 320 samples. The more objective BMR correlated well with the ECC method, showing a correlation coefficient of 0·987 for 406 samples. Direct microscopic counts (DMC) were correlated with a centrifugal method and with a chemical method of preparing samples for electronic cell counting. For 430 samples in each case the correlation coefficients obtained were 0·930 and 0·966 respectively. The 2 ECC techniques were compared using 430 samples, and a very close relationship was found ( r =0·988). For regular examination of large numbers of milk samples using the electronic cell counter we consider the chemical method of sample preparation more suitable than the centrifugal method. Differences in the reproducibility and accuracy of both tests are negligible, but the former procedure is quicker, more economical in terms of cost, and more adaptable to a national testing programme.